Analisis Tantangan dan Solusi Implementasi Kurikulum Merdeka dalam Pembelajaran SD Negeri Jagalampeni 04 - Anggun Setiyaningrum; Turoh Mas’amah; Edi Susanto (Primera Educatia Mandalika: Elementary Education Journal, 2025)
The Independent Curriculum is an effort to reform the world of education that aims to provide a more meaningful and relevant learning experience for students. This study aims to examine the implementation of the Independent Curriculum at SD N Jagalampeni 04, and to identify the challenges and solutions faced in its implementation. This study uses a qualitative method with a case study approach, through in-depth interviews with teachers and students, and classroom observations. The results of the study indicate that the implementation of the Independent Curriculum in this school is running well, with an emphasis on project-based learning and differentiation that allows students to learn according to their style and pace. The advantages of implementing this curriculum are seen in increasing student engagement, character development, and social skills. However, there are several obstacles, such as limited internet access, lack of technology training for teachers, and inadequate facilities and infrastructure. The solutions proposed to overcome these obstacles include intensive training for teachers, increasing access to technology, and providing offline learning materials. In conclusion, the implementation of the Independent Curriculum at SD N Jagalampeni 04 has a positive impact on learning, although further support is needed to overcome the existing challenges. Keywords: Independent Curriculum; Implementation; Differentiated Learning; Challenges; Solutions